Petrogenesis of the tertiary lavas of the Isle of Skye, N. W. Scotland - Scarrow, J (1992)
﻿ The Tertiary lavas of Northern Skye, N.W. Scotland comprise a pile of flat-lying, predominantly basaltic, volcanic flows. The lavas are the earliest products of the igneous activity on Skye, later manifestations including the gabbroic Cuillin complex and the Red Hills granites. The activity occurred from approximately 65 Ma to 50 Ma (Palaeocene to Eocene) within a continental environment. The lava pile can be divided compositionally into three magma-types, the Skye Main Lava Series (SMLS), lavas of which constitute the majority of the pile, and the less abundant Preshal Mhor (PM) and Fairy Bridge (FB). This study concerns the petrogenesis of the three magma-types. The three magma-types have a normal basaltic mineralogy; phenocrysts include olivine, plagioclase and sparse clinopyroxene; groundmasses comprise varying proportions of olivine, plagioclase, clinopyroxene, and titanomagnetite. A typical flow comprises four zones: a basal amygdaloidal layer, a massive central portion possibly showing columnar jointing, a purple rotted amygdaloidal layer, and a capping red or brown bole. The fractional crystallisation of the SMLS w#s a two-stage process initially involving the precipitation of olivine (± minor Cr-spinel), and later fractionation of olivine and plagioclase ± clinopyroxene. The majority of the lavas assimilated some lower crustal Lewisian granulite en route to the surface. The most basic lavas are the most contaminated. Major and trace element modelling suggests that the SMLS magmas were generated by 15 % melting, at an above-average mantle potential temperature, within the spinel-garnet transition zone at a depth of - 100 km. The magmas subsequently last equilibrated with mantle host rocks at 15 kb (- 45 km).